INVENTARISASI POTENSI TEGAKAN POHON PADA HUTAN HAK DI DESA LATOMA JAYA KABUPATEN KONAWE - Rahmah Dzulhajjah; Ikraeni Safitri; Arif Budiman Ashadi (JURNAL AGRIMENT, 2023)
The aim of this research is to find out the potential of tree stands in the private forest of Latoma Village. Research using quantitative, descriptive methods in this study is intended to obtain an overview and information regarding data on the potential of tree stands in private forest areas. From the results of data collection, it was found that the number of trees successfully recorded was a total of 25 tree species, all of which were woody plants in the form of trees (trees) with a diameter class of 20-60 cm. There are 3 types of trees in the private forest, so the dominant trees are in the mixed-species class, Commercial class two, with a percentage of 79%, Meranti wood species class, commercial one class, 18%, and beautiful class two, 3%. It can be seen that the distribution of diameter classes for all species groups is fairly even. with a total volume per plot of 90.35 m^3/Ha, and the total number of trees found was 135 trees. Based on these results, if converted to the total area of Private Forest, the total volume is 10,039.32 m^3/Ha and the total number of trees is 15,000 trees.